The relationship between ventilation and opening strategies of domed mosque for indoor comfort / Fathimah Zakiyah Othman, Sabarinah Sheikh Ahmad and Nurul Liyana Hanapi - Othman, Fathimah Zakiyah; Sheikh Ahmad, Sabarinah; Hanapi, Nurul Liyana (2019)
A mosque is an important communal space for the Muslim community. Instead of focusing on physical aesthetics, mosque designs should be more focused on passive means for indoor comfort such as to study how natural ventilation and envelope designs could improve indoor comfort. This study aims to examine the relationship between ventilation and opening strategies of a domed mosque for indoor comfort in Malaysia. This investigation is done by running wind tunnel simulations on the various domed mosque design strategies and configurations to draw conclusion as to which variation provides the highest rate of air movement within the mosque. The study concludes that openings on domed roofs would be considered a good ventilation inducer and smaller inlet-outlet could provide an alternative for warmer regions with good wind flow. The results of this study provides a basis for future mosque designers to ensure that natural ventilation systems are considered thoroughly, simultaneously taking into account the thermal comfort aspect within their design in order to achieve a sustainable design solution.